Automation of selection and verification of material sizes for packaging systems - Rodriguez-Ugalde, Pablo Javier (2024)
Automation systems in material selection and verification are advanced technology-based systems that allow for labor cost savings and elimination of human errors in these types of processes, improving production and occupational safety within the industry. By employing signal systems and digital logic, an automation method based on sensors is implemented to select and verify different materials’ sizes, specifically for packaging. Various important terms for a better understanding of the different parts that make up such a system and its application will be presented. Additionally, a visual demonstration through software will show the process and results of such a system in more detail, along with relevant recommendations and conclusions.